Early Paleozoic zircon ages of the Higher Himalayan Gneisses of the Everest region and their Pan-African/Proto-Himalayan orogenic signature (Journal of Nepal Geological Society, 2019)
The U-Pb analysis of zircons from two independent leucosome bodies belonging to the paragneiss of the Higher Himalayan Crystallines Sequence (HHCS) in the Everest region of eastern Nepal Himalaya was carried out using laser ablation-multi collector inductively coupled plasma-mass spectrometry (LA-MC-ICP-MS) at the University of Arizona, Tucson, USA. The analysis of zircons from sample 07EVT3 forms a discordia with upper and lower intercepts at 478±25 and 21.5±4.1 Ma with concordant ages of 488.5±9.2 and 20.9±0.9 Ma for cores and rims, respectively. Similarly, the analysis of zircons from sample U1206 forms a discordia with upper and lower intercepts at 515±20 and 34.8±2.7 Ma, and provides concordant ages of 463.9±10.9 and 24.6±0.6 Ma for cores and rims, respectively. No inherited zircon grains with older ages were found indicating that almost all these zircons must have formed along with the leucotomies during the ca. 500 Ma metamorphism of the protoliths. The high U/Th ratio, i.e. average 11.0 for zircons from sample 07EVT3 and 253.6 for sample U1206 also support a metamorphic origin of the zircons. The occurrences of zircons in the ca. 500Ma leucosomes in the HHCS strongly points that rocks in the Himalayan area had undergone to a high-grade metamorphism during the late Pan-African time. We call this metamorphism as the Proto himalayan metamorphism. More studies along this line will help to better understand and constrain the Pan-African orogenic history of the Proto-Himalayan Orogen within the Peri-Gondwana Orogenicterrains.